Design and development of a fiber optic acoustic hydrophone - Lin, Ying. (2009)
An all-fiber-optic hydrophone has been designed, constructed and tested. The fiber system consists of a sensing interferometer and a compensating interferometer with optical path length compensation. The compensating interferometer contains an optical frequency shifter in one of its arms to enable a heterodyne detection and it compensates the optical path length difference caused by the long arm of the sensing interferometer. As a result, the new system configuration offers some unique advantages. The hydrophone is a true heterodyne device. The compensating interferometer is located near the electronics module and is shielded from acoustic interference. The sensing interferometer is completely passive and is remotely located.